2019
DOI: 10.1093/icvts/ivz185
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of aortic remodelling after total arch replacement with frozen elephant trunk for acute aortic dissection

Abstract: OBJECTIVES We investigated the outcomes of total arch replacement with frozen elephant trunk (FET) for Stanford type A acute aortic dissection and the patterns of postoperative aortic remodelling from computed tomographic (CT) findings. METHODS From April 2015 to November 2018, we performed total arch replacement with FET for Stanford type A aortic dissection in 30 patients. Postoperative contrast-enhanced CT showed the posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…Therefore, it is crucial to treat only those patients who are likely to develop negative FL remodeling. To date, CT-based predictors of FL enlargement or negative remodeling have been identified as the number of vessels originating from the FL [ 8 ] and re-entry locations [ 9 ]. However, morphological assessment is limited; this study identified predictive factors by functional evaluation of fluid dynamics using 4D flow MRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is crucial to treat only those patients who are likely to develop negative FL remodeling. To date, CT-based predictors of FL enlargement or negative remodeling have been identified as the number of vessels originating from the FL [ 8 ] and re-entry locations [ 9 ]. However, morphological assessment is limited; this study identified predictive factors by functional evaluation of fluid dynamics using 4D flow MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, this procedure may be feasible to perform in patients at risk of negative aortic remodeling, specifically the expansion of the aorta, especially in the FL region. Though several morphologic predictors based on computed tomography (CT) angiography findings have been employed to detect negative aortic remodeling [ 8 , 9 ], and to the best of our knowledge, those that can be applied for further treatment are lacking. Notably, four-dimensional flow magnetic resonance imaging (4D flow MRI) has allowed us to perform functional analysis of the predictors of negative aortic remodeling [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of aortic remodeling, we found that once there was a tear in the DTA on postoperative CT, aortic remodeling did not occur regardless of the levels of the descending aortic communications between the lumina. 16 In such cases, additional TEVAR is necessary to prevent any adverse aortic events in the downstream aorta. 17 In the present series, aortic remodeling occurred in the stented segment of the aorta in 83% of the patients on postoperative contrast-enhanced CT during the average follow-up of 22 months.…”
Section: Discussionmentioning
confidence: 99%
“…The main risk factor for reintervention on the arch or descending thoracic aorta after proximal aortic repair is the persistent flow in the false lumen, which is associated with aneurysmal degeneration of the dissected aorta (52,55,56). Presence of a tear in the descending aorta on post-operative scans predicts failure of the aorta to remodel (64,65) as these communications between lumina infer pressurization of the false lumen and unlikely false lumen thrombosis (66). Analysis of pre-discharge CT scans after ATAD repair demonstrate additional entry tears in the proximal descending thoracic aorta in 38% of cases, distal descending thoracic aorta in 25% and abdominal aorta in 41% of patients (67).…”
Section: Medium-and Long-term Outcomes-survival Aortic Remodeling and Reoperationmentioning
confidence: 99%
“…In cases where the primary entry tears are located in the aortic arch and/or proximal descending thoracic aorta, arch replacement with FET allows false lumen exclusion leading to false lumen thrombosis and its obliteration (61,65,68). Available long-term data suggest that aortic remodeling with partial or complete thrombosis of the persistent false lumen can be expected in approximately 90% of cases along the length of the stent graft (69)(70)(71).…”
Section: Medium-and Long-term Outcomes-survival Aortic Remodeling and Reoperationmentioning
confidence: 99%